GENERAL MOTIONAL PERFORMANCE OF REPRESENTATIVES IN DANCE SPORT (Fiep Bulletin - online, 2014)
The aim of research was to objectify motion performance of national team members of the Slovak Republic in dance sport. The work is dealing with comparison of resulting parameters of selected motion tests in separate age categories. The test battery consisted of the following tests: jumping from the spot, sitting – lying within 30 seconds, shuffle running10 x 50 metres and exercises from the Jacík’s integral motor test. The research set consisted of members of the national team of the Slovak Republic in dance sport, competing in the age categories of junior I, junior II and youth. The results confirmed statistically significant differences between separate age categories. Acknowledgment: This research was carried out within the grant VE GA 1/0503/11
Keywords: dance sport; motor tests; team members; general motional performance